د ا رسة بعض المعايير الكيموحيوية في مصل دم المصابين بالفشل الكموي المزمن في محافظة كربلاء - الع ا رق - العيساويدلال عبد الحسين كاظم (University of Thi-Qar Journal of Science, 2019)
This study was concluded in laboratories of the Hussien teaching hospital/department of industrial kidney in Karbala governorate during the period between 1/10/2011 to 1/4/2012 to fine the relationship between some biochemical parameters and chronic kidney failure patients men.The study was carried out on (36) men that undergo from failure of the kidney chronic during their admission the hospatital then the results that obtained compared with the control group that included (36) healthy male. The results revealed that a significant increase (p<0.05) in urea, total keratinine and uric acid concentration in blood serum compared with the control group, and a significant increase (p<0.05) in the potassium and sodium ion concentration compared with the control group, but the results showed a significant decrease (p<0.05) in the calcium ion concentration as compared with the control group.